Aspects that Influence the Decision Making Process in Fashion Product Development - Aini, Laila Nur; Zuhria, Maulida Zakiyatuz; Fajar, Maulita; Hidayat N, Rusdi; Kusumasari, Indah Respati (Indonesian Journal Publisher, 2025)
This research examines the aspects that influence the decision-making process in fashion product development. The increasing complexity of consumer preferences and the rapid changes in fashion trends make the decision-making process very crucial in determining product success. The research used a qualitative method with a systematic literature study approach and in-depth interviews with 15 fashion industry practitioners. The results identified five main aspects that influence decision-making: analysis of market trends and consumer preferences, environmental sustainability considerations, production technology capabilities, financial factors and risk management, and design innovation aspects. The analysis showed that the integration of data analytics with a deep understanding of consumer preferences had the most significant influence, contributing 42% to product development success. Environmental sustainability emerged as an increasingly important factor, influencing 28% of consumer purchasing decisions. The research also found that companies that integrate all five aspects into their decision-making process have a 35% higher product success rate than those that only focus on a particular aspect. The results of this study provide a comprehensive framework for fashion industry practitioners to optimize the product development decision-making process.